2012
DOI: 10.5923/j.food.20120204.02
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cassava, Sweet Potato and Cocoyam, and Their By-Products by Non – Ruminants

Abstract: As the search for alternative sources of energy for non ruminants continues, this review was undertaken to examine the potential value of cassava (Manihot utilissima Pohl.), sweet potato (Ipomea batatas Poir.), cocoyam (Xanthosoma sagittifolium Schott.) and their by-products as dietary supplements for non ruminants. Studies on these roots and tubers showed that, on a dry-weight basis, contained 2.0 -7.9% crude protein, 0.3 -3.1% crude fib re and 72.4 -77.9% starch. The practical use of these roots and tubers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
1
27
1
3
Order By: Relevance
“…C and E (Apata & Babalola, 2012 In addition, the values of this study are above the maximum yields observed by Azevedo et al In addition, Brazlândia Branca cultivar also presented higher means for yield.…”
Section: Resultssupporting
confidence: 57%
“…C and E (Apata & Babalola, 2012 In addition, the values of this study are above the maximum yields observed by Azevedo et al In addition, Brazlândia Branca cultivar also presented higher means for yield.…”
Section: Resultssupporting
confidence: 57%
“…Edache, Yisa, and Okpala () reported improved egg production egg qualities and higher economic return in laying quail hens fed 200 g/kg dietary yam peel meal. Inclusion of 200 g/kg sweet potato peel in the diet did not compromise the performance of laying hens (Apata & Babalola, ). Recently, Edache, Tuleun, Yisa, and Muduudtai () observed no differences in feed intake, egg production and qualities between laying quails fed sweet potato peel at 190 g/kg diet and the control diet.…”
Section: Dietary Recommendations Of Peel Meals For Poultrymentioning
confidence: 99%
“…Segundo Apata & Babalola (2012) as plantas de batata-doce possuem boas qualidades nutricionais, sendo superiores a outras fontes utilizadas para a alimentação animal, e consequentemente, tem potencial de utilização na alimentação de animais ruminantes e não-ruminantes. Para a atividade normal das bactérias ruminais são necessários de 6 a 8% de proteína bruta (FIGUEIREDO et al, 2012).…”
Section: Parâmetrosunclassified